THU0152 The Poet-Us Study: Can Ultrasonography Predict Flare in Patients with RA and Persistent Low Disease Activity in Whom the Tnfinhibitor (TNFI) is Stopped? Preliminary Results of an Ongoing Study. (23rd January 2014) - Lamers-Karnebeek, F. B. G.; Jacobs, H.; Fransen, J.; Luime, J.; Riel, P.; Jansen, T.
Abstract : Background: The POEET (Potential Optimalisation of Expediency of TNFi) study is an ongoing study investigating TNFi cessation in RA patients on TNFi and conventional DMARD. Part of this study is the POET-US, investigating whether ultrasonography (US) can predict flare. (1) Objectives: To present preliminary data of the POET-US study in which prediction of flare, defined as DAS28>3.2 and at least > 0.6 increase compared to baseline DAS28, by US at baseline is investigated. Methods: The POETUS study is a multicenter (n=14) randomized prospective cohort study in the Netherlands. Participating patients have RA according to ACR 1987 criteria, DAS28 low disease activity low disease activity (<3.2) > 6 months and have been treated with stable dose TNF-i and conventional DMARD > 1 year. Patients are randomized to continue or stop TNFi; of those who stop US is performed at baseline (MCP 1-5 dorsal & volar, wrists and MTP 2-5 dorsal, all bilaterally). All US-scans are performed with an Esaote MyLab 60 machine and high-frequency, linear transducer. A semi-quantitative synovitis scoring system is used for Grey Scale (GS) and Power Doppler (PD). Grey scale: Grade 0: normal; Grade 1: elevated capsule, below the joint boundaries; Grade 2: elevated capsule above the joint boundaries, <50% convex; Grade 3: elevated capsule above the joint boundaries, > 50% convex. Power Doppler: Grade 0: no PD signal; Grade 1: few single PD signals; Grade 2: merging PD signals, < 50% of the synovial space; Grade 3: PD signal in > 50% of the synovial space. GS and PD scores of individual joints were summed; as grade 1 GS occured very frequently this was recoded to grade 0. Also baseline laboratory parameters and RA characteristics are recorded. The presented data are preliminary data from 2 centers (Utrecht, Nijmegen). Results: 53 patients were included, 9 (17%) flared. Mean (sd) follow-up of all patients was 106 (79) days; mean (sd) time until flare was 77 (46) days. Conclusions: Our preliminary results with limited data show that PD US and CRP, both assessed at cessation of TNFi in low disease activity RA, may predict future flare. Analysis of all data at completion of the study is necessary to corroborate these results. References: Disclosure of Interest: F. Lamers-Karnebeek Grant/research support from: Abbott, H. Jacobs: None Declared, J. Fransen: None Declared, J. Luime: None Declared, P. Riel: None Declared, T. Jansen: None Declared